Characterization of Renal Injury and Inflammation in an Experimental Model of Intravascular Hemolysis - Merle, Nicolas S.; Grunenwald, Anne; Figueres, Marie-Lucile; Chauvet, Sophie; Daugan, Marie; Knockaert, Samantha; Robe-Rybkine, Tania; Noe, Remi; May, Olivia; Frimat, Marie; Brinkman, Nathan; Gentinetta, Thomas; et al. (Frontiers in Immunology, 2018)
Intravascular erythrocyte destruction, accompanied by the release of pro-oxidative and pro-inflammatory components hemoglobin and heme, is a common event in the pathogenesis of numerous diseases with heterogeneous etiology and clinical features. A frequent adverse effect related to massive hemolysis is the renal injury and inflammation. Nevertheless, it is still unclear whether heme – a danger-associated molecular pattern and ligand for TLR4 or upstream hemolysis-derived products are responsible for these effects. Well-characterized animal models of hemolysis with kidney impairment are needed to investigate how hemolysis drives kidney injury and to test novel therapeutic strategies. Here we characterized the pathological processes leading to acute kidney injury and inflammation during massive intravascular hemolysis, using a mouse model of phenylhydrazine (PHZ)-triggered erythrocyte destruction. We observed profound changes in mRNA levels for markers of tubular damage (Kim-1, NGAL) and regeneration (indirect marker of tubular injury, Ki-67), and tissue and vascular inflammation (IL-6, E-selectin, P-selectin, ICAM-1) in kidneys of PHZ-treated mice, associated with ultrastructural signs of tubular injury. Moreover, mass spectrometry revealed presence of markers of tubular damage in urine, including meprin-a, cytoskeletal keratins, a-1-antitrypsin and a-1-microglobulin. Signs of renal injury and inflammation rapidly resolved and the renal function was preserved, despite major changes in metabolic parameters of PHZ-injected animals. Mechanistically, renal alterations were largely heme-independent, since injection of free heme could not reproduce them, and scavenging heme with hemopexin in PHZ-administered mice could not prevent them. Reduced overall health status of the mice suggested multi-organ involvement. We detected amylasemia and amylasuria, two markers of acute pancreatitis. We also provide detailed characterization of renal manifestations associated with acute intravascular hemolysis, which may be mediated by hemolysis-derived products upstream of heme release. This analysis provides a platform for further investigations of hemolytic diseases and associated renal injury and the evaluation of novel therapeutic strategies that target intravascular hemolysis.